2016
DOI: 10.1002/jbmr.3001
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte-Secreted Wnt Signaling Inhibitor Sclerostin Contributes to Beige Adipogenesis in Peripheral Fat Depots

Abstract: Cells of the osteoblast lineage are increasingly identified as participants in whole-body metabolism by primarily targeting pancreatic insulin secretion or consuming energy. Osteocytes, the most abundant bone cells, secrete a Wnt-signaling inhibitor called sclerostin. Here we examined three mouse models expressing high sclerostin levels, achieved through constitutive or inducible loss of the stimulatory subunit of G-proteins (Gsα in mature osteoblasts and/or osteocytes). These mice showed progressive loss of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 63 publications
7
85
0
Order By: Relevance
“…Communication between adjacent osteocytes and neighboring cells is mediated by gap junctions. In addition, osteocytes can signal to distant cells or organs via secreted factors released in the bone marrow space or directly into the circulation (8). Their location, deeply into the mineralized bone, and their structural organization of a cellular network, make them ideal to sense mechanical stimuli and to transduce these signals into biochemical cues affecting the surrounding cells.…”
Section: Osteocytesmentioning
confidence: 99%
“…Communication between adjacent osteocytes and neighboring cells is mediated by gap junctions. In addition, osteocytes can signal to distant cells or organs via secreted factors released in the bone marrow space or directly into the circulation (8). Their location, deeply into the mineralized bone, and their structural organization of a cellular network, make them ideal to sense mechanical stimuli and to transduce these signals into biochemical cues affecting the surrounding cells.…”
Section: Osteocytesmentioning
confidence: 99%
“…Our group recently started to use ex vivo fat and pancreas organ cultures to investigate the cross‐talk between bone and fat, and bone and pancreas. Growing evidence suggests that bone‐derived sclerostin regulates body composition and glucose metabolism . We found that mice with elevated circulating sclerostin exhibit increased peripheral white fat mass and upregulation of genes involved in mitochondrial respiration and biogenesis including Pgc1α, Ucp1, or Prdm16.…”
Section: Other Ex Vivo Organ Culturesmentioning
confidence: 83%
“…The skeleton is emerging as an important endocrine organ implicated in the regulation of whole‐body composition and glucose metabolism . Similarly, bone and muscle communication has been a major focus of musculoskeletal research in the recent years .…”
Section: Other Ex Vivo Organ Culturesmentioning
confidence: 99%
“…Bone‐derived factors also play a role in browning. The osteocyte‐secreted factor sclerostin , normally associated with osteoporosis, contributes to increased beige adipogenesis in vivo and in vitro (Fulzele et al, ). To demonstrate the effect of sclerostin, Fulzele et al engineered an osteocytic cell line lacking Gsα to express and secrete high levels of sclerostin.…”
Section: Proteins/peptidesmentioning
confidence: 99%